HUBUNGAN PERILAKU PEMAKAIAN LAPTOP DENGAN KEJADIAN COMPUTER VISION SYNDROME (CVS) PADA MAHASISWA ANGKATAN 2009 PSIK FAKULTAS ILMU KESEHATAN UNIVERSITAS TRIBHUWANA TUNGGADEWI MALANG - Ani Sutriningsih; Megawati Nur Anggareni (Care : Jurnal Ilmiah Ilmu Kesehatan, 2014)
Laptop usage can cause a health complaint called Computer Vision Syndrome (CVS). This syndrome is influenced from the application of ergonomics system that is not good for students use the laptops. The purpose of this study is to identify and analyze the laptop usage behaviour with the case (happenings) of Computer Vision Syndrome (CVS) in Student Year 2009 Nursing Science Program Faculty of Health Sciences University of Tribhuwana Tunggadewi Malang. This study is a descriptive correlative study with the cross sectional method. Sampling technique is Simple random sampling with a sample of 67 respondents. Data collection by questionnaire. The results showed respondents had less good laptop usage behaviour: 37 people (55.2%), the negative Computer Vision Syndrome (CVS): 40 (59.7%) and based on the results of the Spearman Rank correlation test with 95% significance p values obtained: 0.000. This value less than alpha value 0.05 means Ho is rejected so in statistical tests in this study stated there was a significant relationship between the laptop usage behaviour with Computer Vision Syndrome (CVS) case in Student Year 2009 Nursing Science Program University of Tribhuwana Tunggadewi Malang. Based on the above results, for further researcher could be assessed about the relationship of laptop usage behavior with the visual acuity (visual sharpness). Information about the correct laptop usage behaviour and their impact needs to be widely socialized so that laptop users can be avoided from the happening of CVS.